Efficacy of dexamethasone or clonidine as adjuvants in interscalene brachial plexus block for preventing rebound pain after shoulder surgery: a randomized clinical trial - Layana Vieira Nobre; Leonardo Henrique Cunha Ferraro; Juscelino Afonso de Oliveira Júnior; Vitória Luiza Locatelli Winkeler; Luis Flávio França Vinhosa Muniz; Hiago Parreão Braga; Plínio da Cunha Leal (Brazilian Journal of Anesthesiology)
Background: Rebound pain is believed to involve both nociceptive pain due to insufficient analgesia and hyperalgesia induced by regional anesthesia. Adjuvant's addition could prevent rebound pain. This study aimed to determine if the addition of dexamethasone or clonidine to local anesthetic when performing interscalene block could prevent rebound pain. Methods: This was a multicenter, prospective, parallel grouping, randomized clinical trial conducted with patients receiving a single injection of bupivacaine 0.375% in interscalene block ultrasound guided and general anesthesia for shoulder surgery were randomly assigned to either no additives (control), clonidine (30 mcg), or dexamethasone (4 mg). The primary outcome was rebound pain, defined as sudden onset of pain, moderate to severe intensity (VAS ≥7) without improvement with oral medication, followed by VAS pain at rest, required rescue analgesia, the occurrence of adverse events or complications, and satisfaction survey assessments between groups. Rebound pain and pain at rest were assessed 2, 4, 6, 12, 24, and 48 hours after the procedure. Results: The incidence of rebound pain was not statistically different between groups (p-value = 0.22), with an observed incidence of 41.2% (95% CI 25.9‒57.9), 28.6% (95% CI 16.7‒43.3), and 23.3% (95% CI 12.6‒37.6) in the control, dexamethasone, and clonidine groups, respectively. Additionally, there were no significant differences between the groups in time, from anesthetic blockade to first complaint of pain or the severity of postoperative pain. Conclusion: The administration of dexamethasone or clonidine as perineural adjuncts to local anesthesia in single-injection interscalene blocks did not significantly reduce the incidence of rebound pain.